COVID-19 triggered systemic lupus erythematosus in a child: a case report - Maram, Krishna Prasad; Paturi, Venkata Rama Rao; Alla, Lalitha Sudha; Bhagavatula, Murali Krishna (International Journal of Contemporary Pediatrics, 2021)
The COVID-19 pandemic has continued to wreak havoc globally during the second wave. Even though it tends to be asymptomatic or cause only a trivial illness in children, it is reported to be associated with a delayed hyper-inflammatory response syndrome resulting in multi-organ dysfunction in children. It is possible that through unknown mechanisms, it could also result in triggering of other auto-immune disorders. We report a case of pediatric systemic lupus erythematosus (SLE) with lupus nephritis suspected to be triggered by SARS-CoV-2 virus which is not reported in the literature so far.